Survey experiments and aerial survey of elephants in the South Luangwa National Park and the Lupande Game Management Area, Zambia, 1993 - Hugo Jachmann (Pachyderm)
Describes the survey methodology and compares the data focussing on the observer bias from aerial surveys undertaken in 1993. A estimated population of 6,000 elephants occupy the South Luangwa National Park and Lupande Game Management area including the Nsefu area along the Luangwa River in the northwest corner of the Upper Lupande section.